The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/mcg.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

The Short Health Scale

Abstract: SHS is a health measure that shows promising evidence of validity, reliability, and responsiveness in IBS patients. It is quickly completed and evaluated, which supports its usefulness in the busy clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…All these results taken together highlight the importance of taking into consideration the differences that occur when it is self-reported or clinician-rated [47]. Relatedly, subjective health assessment by patients might give gastroenterologists additional information about their overall clinical picture [48]. Incongruences between clinician's and patients perceptions of quality of life have been found in medical conditions such as multiple sclerosis [49], asthma [24], or hip arthroplasty [50], and seems to be related with different clinical outcomes such as macular degeneration [51,52].…”
Section: Discussionmentioning
confidence: 89%
“…All these results taken together highlight the importance of taking into consideration the differences that occur when it is self-reported or clinician-rated [47]. Relatedly, subjective health assessment by patients might give gastroenterologists additional information about their overall clinical picture [48]. Incongruences between clinician's and patients perceptions of quality of life have been found in medical conditions such as multiple sclerosis [49], asthma [24], or hip arthroplasty [50], and seems to be related with different clinical outcomes such as macular degeneration [51,52].…”
Section: Discussionmentioning
confidence: 89%
“…The questionnaires Short Health Scale, Short Form 36 version 2, the gastrointestinal symptom rating scale and a Rome version III questionnaire on functional gastrointestinal disorders were answered. 33,34 During the six days between the two hospital visits for SeHCAT testing, the patients recorded stool habits using a structured diary with Bristol stool scale pictograms. The patients could collect a voluntary random stool sample at home to be immediately frozen below −18 degrees Celsius.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this tionnaire, first used in Swedish in 2002, can be used in UC in 2006 and and came into use. 10,11,12,[15][16][17][18][19] This study demonstrated that the SHS can also be used in Turkish-speaking patients.…”
Section: Discussionmentioning
confidence: 99%